Implementing School Literacy Movement through JuMaDi - Winarsih, Sri (English Department, Universitas Negeri Surabaya, 2021)
This research aims to examine the implementation of one of the school literacy programs implemented by SD Al-Khodijah Merauke which had been proposed by the researcher team that is JuMaDi. JuMaDi stands for Jumat Majalah Dinding or Friday Wall Magazine. The research was conducted in SD Al-Khodijah Merauke with the research object was all students at third graders in the number of 23 students and 3 in responsible teachers for wall magazine management. The technical triangulation was used by combining disguised observation and semi-structured interview and documentation in collecting the data. Then, the data were analysed by the technique of Miles and Hubermans three steps; reduction, display, and verification. The result of the research shows that JuMaDi has been managed well by the teachers and responded enthusiastically by the students. Three points observed from the program; 1) The Form; Thematic (recount, retold narrative, poem, and letter). 2) The Procedure; theme announcement, deadline submission, selection, and publication. 3) The Result; The students participation of Recount at 1st Friday got 61% with the most topic œI Went to, Retold Narrative at 2nd Friday got 74% with the most topic œProphets Story, Poem at 3rd Friday got 82% with the most topic œMother, and Letter for Teacher got 87% with the most topic œGratitude. JuMaDi does not only encourage the spirit of literacy but also accustom students to be positively competitive.Keywords: elementary school, implementation, literacy, wall magazine, school literacy